Originally Posted by
fardeen_gen \sum\limits_{n = 0}^{ \infty } {\frac{1}{n!}\left[\sum\limits_{k = 0}^{n} {(k + 1)\left(\int_0^1 2^{-(k + 1)x}\ dx\right)\right]8}}
This isn't working! Why?
I don't know why, but for some reason the compiler doesn't like the unnecessary braces that you have used to wrap around some sections of the formula. Remove the red ones in this code\sum\limits_{n = 0}^{ \infty } {\frac{1}{n!}\left[\sum\limits_{k = 0}^{n} {(k + 1)\left(\int_0^1 2^{-(k + 1)x}\ dx\right)\right]8}}
and you get $\displaystyle \sum_{n = 0}^{ \infty } \frac{1}{n!} \left[\sum_{k = 0}^{n}(k + 1)\left(\int_0^1 2^{-(k + 1)x}\, dx\right)\right]8 $
(And it looks as though the 8 probably shouldn't be there at all?)
Also note that you don't need to use \limits with \sum. They are supplied automatically.